2013
DOI: 10.4269/ajtmh.2012.12-0227
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Genotypes in Mepraia gajardoi from Wild Ecotopes in Northern Chile

Abstract: Abstract. We evaluated Trypanosoma cruzi infection in 397 wild Mepraia gajardoi specimens from five coastal localities in northern Chile by detection of minicircle DNA by polymerase chain reaction. The wild capture sites were classified into two ecotopes: a fully wild ecotope (ecotope 1) and a wild ecotope near human dwellings (ecotope 2). Infection rates varied between 11% and 27%. Minicircle hybridization assays showed that T. cruzi lineages Tc II and Tc VI were commonly detected in ecotope 1 and ecotope 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…() in the same sampled sections; although the differences in infection found by Toledo et al . () could be explained by the fact that most of our specimens collected in San Marcos were associated with birds, in which the parasite does not reproduce owing to the mechanism of natural resistance to the parasite (Kierszenbaum et al, ).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…() in the same sampled sections; although the differences in infection found by Toledo et al . () could be explained by the fact that most of our specimens collected in San Marcos were associated with birds, in which the parasite does not reproduce owing to the mechanism of natural resistance to the parasite (Kierszenbaum et al, ).…”
Section: Discussionmentioning
confidence: 74%
“…This value could be explained by the low prevalence of the parasite in the insect vectors found in this study (5.8%). Previous studies reported variables infection rates of M. gajardoi between 11 and 27% in different localities of Region XV and Region I (Carvajal et al ., ; Botto‐Mahan et al, ; Jercic et al ., ; Toledo et al ., ). These rates are lower than those found in M. spinolai .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sagua et al () collected 95 specimens of M. spinolai, including adults and nymphs of all five instars in Pan de Azúcar, an island that lies between the regions of Antofagasta and Atacama in northern Chile. Toledo et al () collected 397 adults and nymphs of M. gajardoi at five locations in the coastal region of northern Chile. Campos et al () collected 65 of M. gajardoi , 27 of M. parapatrica, and 72 of M. spinolai , including adults and nymphs, in 13 localities located between 18º and 33º S of the coastal region and valleys in the interior of Chile.…”
Section: Information On Collections Of Three Species Of Mepraia In Chmentioning
confidence: 99%